2018
DOI: 10.1016/j.scriptamat.2018.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous complexions enable a new region of high temperature stability in nanocrystalline Ni-W

Abstract: Solute segregation is used to limit grain growth in nanocrystalline metals, but this stabilization often breaks down at high temperatures. Amorphous intergranular films can form in certain alloys at sufficiently high temperatures, providing a possible alternative route to lower grain boundary energy and therefore limit grain growth. In this study, nanocrystalline Ni-W that is annealed at temperatures of 1000 °C and above, then rapidly quenched, is found to contain amorphous intergranular films. These complexio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…This finding is in agreement with previously reported results from a study of a binary Cu-Zr alloy [28,29]. The formation of AIFs has also been achieved in a variety of other metallic alloy systems, such as Mo-Ni [26], Ni-W [52], and Cu-Hf [32], with no abnormal grain growth reported.…”
Section: Microstructural Evolution During Annealingsupporting
confidence: 92%
“…This finding is in agreement with previously reported results from a study of a binary Cu-Zr alloy [28,29]. The formation of AIFs has also been achieved in a variety of other metallic alloy systems, such as Mo-Ni [26], Ni-W [52], and Cu-Hf [32], with no abnormal grain growth reported.…”
Section: Microstructural Evolution During Annealingsupporting
confidence: 92%
“…11,12 This potential lack of thermal stability, even at room temperature, 5,6 can lead to a degradation of strength over time. To address these limitations, there are several methods to improve thermal and/or mechanical properties, including the use of grain boundary engineered nanocrystalline metals such as nanotwinned metals, [13][14][15] the use of a bimodal grain structures, [16][17][18] the incorporation of amorphous grain boundaries in the material, [19][20][21] orof specific interest to this study the use alloyed nanocrystalline metals that display solute segregation. [22][23][24][25] Other studies have examined the role of alloy-ing on solute drag and Zener pinning, as well as grain boundary segregation, grain refinement, and thermodynamic stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…AIFs strongly resist grain growth, so much that even when nanocrystalline ball milled Cu-Zr containing AIFs was held at 98% of its solidus temperature for a week, it remained nanocrystalline [23]. In fact, Schuler et al [35] even observed a new regime of high temperature nanocrystalline stability due to AIF formation in Ni-W alloys. The ability of AIFs to both stabilize the grain size and diffuse local grain boundary strain concentrations may contribute to the absence of grain coarsening in the AIF-containing sample at fatigue crack nucleation.…”
Section: Resultsmentioning
confidence: 99%